FAKTOR-FAKTOR YANG MEMPENGARUHI VOLUME PERDAGANGAN SAHAM - Hidayatullah, Siti Rahmi; Nuraini, Miranda; Sinurat, Honesty; Fawziah, Intan Nurbaiti (Universitas Trilogi, 2024)
This study aims to analyze the effect of stock returns, return on assets, economic value added, current ratio, dividend payout ratio, and cash flow on stock trading volume in manufacturing companies listed on the IDX for the 2015-2019 period. This research is a quantitative study. The sampling technique in this study is a purposive sampling technique with a sample size of 30 manufacturing companies listed on the IDX. This study was analyzed using multiple linear regression methods. The results of this study indicate that partially economic value added and cash flow have a significant effect on stock trading volume, while stock returns, return on assets, current ratio, and dividend payout ratio do not have a significant effect on stock trading volume. Then simultaneously stock returns, return on assets, economic value added, current ratio, dividend payout ratio and cash flow have a significant effect on stock trading volume.Keywords: Stock Trading Volume, Stock Return, Return on Asset, Economic Value Added, Dividend Payout Ratio, and Cash Flow